KAJIAN TEOLOGIS TENTANG DOKTRIN TRINITAS DALAM PERSPEKTIF TEOLOGI REFORMED DAN IMPLIKASINYA BAGI IMAN KRISTEN - Nova Saputro (GENEVA: Jurnal Teologi dan Misi, 2021)
The doctrine of the Trinity is one of the important and fundamental teachings in the Christian faith. However, it must be admitted that this doctrine is complicated and not easy to understand. So that most Christians even God's servants try to avoid discussing this topic. They consider the Trinity Doctrine to be a difficult topic and is the domain of academics. Not surprisingly, some Christians can only affirm the formulation of this doctrine, without having a good and correct understanding. So that in the end it is difficult for Christians to apply it in daily life. The failure to see the practical aspects of this doctrine is due to several factors. First, there is confusion in understanding this doctrine. Second, the inability to appreciate the divine mystery in this doctrine. Third, the reluctance to take the doctrine of the Trinity on a popular level. Through this article, the writer wants to examine that by understanding the doctrine of the Trinity in the perspective of Reformed Theology correctly and comprehensively, we as Christians can apply the doctrine of the Trinity in daily life with the right perspective. This writing uses literature study or literature study (book research). Considering the topic of the author's discussion is contained in the subject of doctrinal studies, so it is in dire need of data related to the Bible, reference books from the perspective of Reformed Theology. Based on the object of this research study, the author will go through several stages to obtain data to be discussed, among others: first, record several discussions about the doctrine of the Trinity contained in the Bible, theological books in the perspective of Reformed Theology. Second, the author looks for references regarding the application of the doctrine of the Trinity in the lives of believers through the latest books and journals or writings. Third, analyze the findings and the fourth author draws a conclusion from the results of the discussion.